SISTEM MONITORING REALTIME GAS CO PADA ASAP ROKOK BERBASIS MIKROKONTROLER - Sri Zholeha Wulandari; Ali Basrah Pulungan; Hamdani Hamdani (Universitas Negeri Padang, 2019)
This article discusses about system of monitoring levels of gases CO in cigarette smoke in real time using Labview software. This monitoring system can provide information on CO gas levels of smoking, this tool is planned to be used in place of the public. The process of testing done by giving the value of the voltage sensor. That voltage sensor MQ-2 influence the levels of CO gas in cigarette smoke, namely voltage 0.1 Volts to 5 Volts affect 200-10000PPM. These results are similar to the characteristics of the sensor MQ-2. So it can be inferred the design tools can work well.